THE ROLE OF COLLABORATION VALUE CHAIN DESIGN AT REWARD-BASED CROWDFUNDING PLATFORMS AND MUSIC INDUSTRY IN INDONESIA - Octadila Laily Anggraeni; Elvia Shauki (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
Industry 4.0 has brought many changes, in the financial sector there is financial technology. One form of financial technology is crowdfunding. Creative industries are quite high sectors that use crowdfunding as a funding model. This research includes collaboration between crowdfunding and the music industry. In the process of collaboration between the crowdfunding and the music industry, the parties need to conduct a value chain analysis and find out their competitive advantages to maximize fundraising. The consequence of collaboration between the crowdfunding and the music industry is the presence of new business models accompanied by changes in the value chain. This study aims to determine value chain design collaboration between reward-based crowdfunding and the music industry. This research is based on the value network theory, using a qualitative approach with multi-cases study design. This research was conducted by gathering information through interviews with crowdfunding and the music industry. The results show that collaboration leads to changes in value chain design. Crowdfunding has changed the pattern of production in the music industry with its involvement in funding, sales, and distribution. Other forms of crowdfunding and other creative industries require further investigation. This study aims to help practitioners understand how reward-based crowdfunding is changing the music industry.